The role and effectiveness of augmented reality in patient education: A systematic review of the literature - Urlings, Julie; Sezer, Sümeyye; ter Laan, Mark; Bartels, Ronald; Maal, Thomas; Boogaarts, Jeroen; Henssen, Dylan (Patient Education and Counseling, 2022)
Objectives To provide an overview of the existing research concerning the use and effects of AR in patient education. Methods Following PRISMA guidelines four electronic databases were systematically searched. Inclusion criteria: empirical studies using any type of AR intervention in patient education across all medical specialties. Quality assessment of the retrieved literature was carried out. Results Ten papers, comprising 788 patients, were identified and included (Randomized controlled trial (RCT)(n = 3), non-randomized controlled trial (n = 3), before-and-after study (n = 3), and qualitative survey (n = 1)). Retrieved literature showed itself to be highly heterogeneous. The studied population included patients suffering from a diverse spectrum of chronic diseases (e.g., prostate cancer, diabetes mellitus, multiple sclerosis, epilepsy). Quantitative results indicated that the use of AR had a positive effect on knowledge retention and patient satisfaction. Qualitative findings suggested that patients liked the technology and felt comfortable with its use for educational purposes. The quality of the retrieved results was shown to be moderate to low. Conclusion The limited evidence of this topic suggests the possible potential of AR in patient education. Practice implication More research, using high-quality study designs and more evidence-based interventions, is needed to fully appreciate the value of AR on patient education.
Keywords: AR; Augmented reality; Chronic disease; Knowledge retention; Patient education; Patient satisfaction; Systematic review